Pre-coupling of receptor oligomers and signaling molecules - Ferré, Sergi (Henry Stewart Talks, 2019)
Pre-coupling of GPCRs with G proteins and adenylyl cyclase, GPCR homomers and heteromers, GPCR oligomer-dependent allosteric modulations between orthosteric ligands, GPCR heteromer-dependent interactions at the adenylyl cyclase level, The striatal adenosine A2A-dopamine D2 receptor heterotetramer